2008
DOI: 10.1149/1.2940345
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Transfer-Enhanced Semiconductor Substrates by Wafer Bonding and Hydrogen Exfoliation Techniques

Abstract: A transfer-enhanced semiconductor substrate has been demonstrated, integrating a thin InP layer on a Si handle substrate with an imbedded porous silicon layer. A Si wafer was anodized to create a low-density porous surface layer. A thin layer of InP was transferred to the Si handle substrate through wafer bonding and hydrogen-induced exfoliation. High-resolution X-ray diffraction, atomic force microscopy, and transmission electron microscopy characterization showed the structure to have high surface and crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…PSi for LTP applications should have a minimum of stress and structural disorder. In this way the mechanical strength of the membrane is increased and they can sustain further processing [27,28]. We fabricate several DPLs on a silicon substrate with the above-mentioned solutions.…”
Section: Surface Characterization and Crystallinity Of The Dplmentioning
confidence: 99%
“…PSi for LTP applications should have a minimum of stress and structural disorder. In this way the mechanical strength of the membrane is increased and they can sustain further processing [27,28]. We fabricate several DPLs on a silicon substrate with the above-mentioned solutions.…”
Section: Surface Characterization and Crystallinity Of The Dplmentioning
confidence: 99%
“…By using H implantation, Jalaguier et al (164) and Tong et al (165) were the first to demonstrate the transfer of three-inch GaAs and InP thin layers onto oxidized Si substrates. Following these pioneering works, research groups at SOITEC/LETI, UCLA, UCSD, Caltech, and MPI-Halle have reported the splitting of InP and GaAs thin layers with a diameter up to four inches by using H and/or He implantation (68,(164)(165)(166)(167)(168)(169)(170)(171). The typical optimal implantation fluences range from 5 × 10 16 to 1 × 10 17 atom cm −2 for ion energies in the 50-150-keV range.…”
Section: Ion Cutting Of Inp and Gaasmentioning
confidence: 99%
“…By using H implantation, Jalaguier et al (39) and Tong et al (40) were the first to demonstrate the transfer of three-inch GaAs and InP thin layers onto oxidized Si substrates. Following these pioneering works, research groups at SOITEC/LETI, UCLA, UCSD, Caltech, and MPI-Halle have reported the splitting of InP and GaAs thin layers with a diameter up to four inches by using H and/or He implantation (19,(39)(40)(41)(42)(43)(44)(45)(46). Figures 3-6 show examples of successful application of the ion-cut process to transfer semiconductor thin layers onto Si wafers.…”
Section: Ultrathin Layer Splitting By Ion-cut Processmentioning
confidence: 99%